2008
DOI: 10.1007/s11604-007-0212-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective induction hyperthermia following transcatheter arterial embolization with a mixture of nano-sized magnetic particles (ferucarbotran) and embolic materials: feasibility study in rabbits

Abstract: IH following TAE with a mixture of ferucarbotran and lipiodol was capable of inducing selective hyperthermia with our device. However, further investigation is needed to confirm its safety and effectiveness in the treatment of malignant neoplasms in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…Two weeks after tumor implantation, when the tumor diameter reached approximately 7-8 mm in diameter, the animals were evenly divided into 4 groups according to the injected agents: group A (n = 4) injected with normal saline, group B (n = 5) with doxorubicin (4 mg/kg), group C (n = 5) with Resovist (Fe 111.6 mg/kg), and group D (n = 5) with the Resovist/doxorubicin complex (Fe 111.6 mg/kg, doxorubicin 4 mg/kg). As the lethal dose of ferucarbotran solution in rodents was reported to be in excess of 558 mg Fe/kg [14], our dosage of Resovist was within the safe range. All therapeutic agents were dissolved in the same volume of saline (0.1 ml) and injected directly into the core of tumors.…”
Section: Preparation Of the Animal Modelmentioning
confidence: 78%
See 1 more Smart Citation
“…Two weeks after tumor implantation, when the tumor diameter reached approximately 7-8 mm in diameter, the animals were evenly divided into 4 groups according to the injected agents: group A (n = 4) injected with normal saline, group B (n = 5) with doxorubicin (4 mg/kg), group C (n = 5) with Resovist (Fe 111.6 mg/kg), and group D (n = 5) with the Resovist/doxorubicin complex (Fe 111.6 mg/kg, doxorubicin 4 mg/kg). As the lethal dose of ferucarbotran solution in rodents was reported to be in excess of 558 mg Fe/kg [14], our dosage of Resovist was within the safe range. All therapeutic agents were dissolved in the same volume of saline (0.1 ml) and injected directly into the core of tumors.…”
Section: Preparation Of the Animal Modelmentioning
confidence: 78%
“…Among the many MNPs, Resovist is clinically approved for contrast-enhanced MR in human [11] and was previously reported to generate effective heat in AMF [14].…”
Section: Discussionmentioning
confidence: 99%
“…Moroz et al [15] assessed the use of ferromagnetic embolization hyperthermia, which consists of arterially embolizing liver tumors with ferromagnetic particles in a rabbit liver tumor model, and they reported that hepatic arterial infusion of lipiodol-containing ferromagnetic particles can result in excellent targeting of liver tumors with hyperthermia in the subsequent application of AMF. Recently, Takamatsu et al [16] evaluated the possibility of selective hyperthermia following transcatheter arterial embolization (TAE) with a mixture of Resovist Ò and lipiodol by using rabbits implanted with renal VX2 carcinoma, and they reported that this technique could induce selective hyperthermia of embolized organs and a higher ratio of apoptosis of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are few reports on the feasibility of magnetic hyperthermia with the use of Resovist Ò except for a report by Takamatsu et al [16]. Our purpose of this study was to present simulation and experimental studies on magnetic hyperthermia with the use of Resovist Ò under the assumption that MNPs are injected into the tumor tissue directly or via TAE.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic nanoparticles may be infused intravenously. Furthermore, percutaneous intratumoral and catheter-directed intraarterial delivery of these agents have been described (56,57). Gold nanoshells, or quantum dots, absorb near infrared light and are capable of producing lethal heat (58).…”
Section: Nanotechnologies For Cancer Therapymentioning
confidence: 99%